Life Skill Development of Oklahoma 4-H Alumni - Sarah E. Maass; Carolyn S. Wilken; Joy Jordan; Gerald Culen; Nick Place (EDIS)
4H-REF-01, an 11-page report by Sarah E. Maass, Carolyn S. Wilken, Joy Jordan, Gerald Cullen, and Nick Place, presents the results of a study assessing the effect of long-term 4-H participation on the development of life-skill competencies, specifically critical thinking, goal setting, communication, cooperation, conflict resolution, problem solving, decision making, and community service. Published through the UF 4-H Youth Development Program, May 2006.